POST-ACCREDITATION EFFICACY IN PUBLIC HEALTH INTERVENTIONS: A QUALITATIVE INQUIRY INTO COMMUNITY HEALTH CENTERS' PERFORMANCE - -, Syamsuddin; Ma'rufi, Ma'rufi; zamli, zamli (Indonesian Journal for Health Sciences, 2025)
Community Health Efforts (CHE) function as primary healthcare services with a predominant emphasis on preventive and promotive measures. This study addresses the issue of the performance efficacy of the Community Health Efforts (CHE)Program at the Katoi Community Health Center (Puskesmas) in North KolakaRegency following accreditation. This research aims to elucidate and critically analyze the performance of the Community Health Initiatives post-accreditation at Katoi Community Health Center. Employing a descriptive methodology with a qualitative approach, the study incorporates in-depth interviews, systematic observations, and comprehensive documentation. The collected data were subjected to analysis through processes of data reduction, data display, and conclusion drawing. The findings reveal that the performance of the Health Promotion, Environmental Health, Family Health, and Community Nutrition programs is classified as Excellent, whereas the performance of the Disease Prevention and Control program is rated as Satisfactory. Additionally, there is a discernible correlation between the accreditation status of the community health center and the performance metrics of the CHE program at Katoi Community Health CenterCommunity Health Efforts (CHE) function as primary healthcare services with a predominant emphasis on preventive and promotive measures. This study addresses the issue of the performance efficacy of the Community Health Efforts (CHE)Program at the Katoi Community Health Center (Puskesmas) in North KolakaRegency following accreditation. This research aims to elucidate and critically analyze the performance of the Community Health Initiatives post-accreditation at Katoi Community Health Center. Employing a descriptive methodology with a qualitative approach, the study incorporates in-depth interviews, systematic observations, and comprehensive documentation. The collected data were subjected to analysis through processes of data reduction, data display, and conclusion drawing. The findings reveal that the performance of the Health Promotion, Environmental Health, Family Health, and Community Nutrition programs is classified as Excellent, whereas the performance of the Disease Prevention and Control program is rated as Satisfactory. Additionally, there is a discernible correlation between the accreditation status of the community health center and the performance metrics of the CHE program at Katoi Community Health Center